5 - Masoala Madagascar : L’histoire de nos origines, retrouvée dans les mémoires collectives - Chaplain TOTO, (Identity, Culture and Politics, 2018)
Masoala Madagascar: The history of our origins, found in collective memories In Madagascar human settlement history, Islamized waves of migrants landed in the northern part of the island between the 9th and the 13th centuries, according to archaeological discoveries in the 70’s. The historical reconstruction of the origins of a group located at the tip of the Masoala peninsula reveals its direct link with the Arabic world. The oral history preserves the details of the course of those migrants until their landing in the host country and their turbulent relations with the indigenous groups. Ancestral practices reveal that these migrants of Arab-Muslim origin landed throughout the Bay of Antongil.